Acute Viral Hepatitis in Diabetic and Nondiabetic Patients: Variable Outcomes - Durga Lohana, Ayzaz Ismail, Muhammad Nouman Aslam, Muhammad Azam, Ayesha Masood, (Pakistan Journal of Medical & Health Sciences, 2022)
Diabetes mellitus is frequent in Pakistan, which is also notorious for severe viral hepatitis epidemics on a regular basis. According to the present study, the clinical results of acute hepatitis B with and without diabetes were compared. Place and Duration: This is cross-sectional descriptive study was held in the Medicine department of M. Islam Medical and Dental College Gujranwala for one-year duration from January 2021 to December 2021. Methods: Patients with diabetes (n = 110, A group) and those without diabetes (n = 120, B group) were divided into two groups of 230 AVH patients. Age, gender, and alanine aminotransferase (ALT) levels did not vary significantly between the two groups. All patients were monitored for a period of 12 months or until they were completely cured. Upper gastrointestinal endoscopy was conducted on all of the patients in order to provide greater insight into the development of potential problems. In addition, abdominal ultrasonography was performed on all of the patients. Results: 90 and 100 of the AVH cases in groups A and B were caused by the hepatitis E virus, respectively. Only 9 of 120 patients in group B had jaundice that lasted longer than 6 months, compared to 40 of 110 (36.4%) of patients in group A. I In both groups, HEV was the primary cause of AVH (group A: (81.9%); group B: (83.3 percent). In both groups, HBV was the second most common cause of AVH. Two patients in group B developed AVH as a result of HAV. In several individuals, the etiological cause of AVH was unknown. Conclusion: According to the results of this study, all patients with diabetes and acute viral hepatitis (AVH) should be continuously observed because there is a danger of severe liver damage and even death in these individuals.